War in Peacetime: Authorship between Bachmann and Ungaretti (Konturen, 2019)
The following reflections contribute to an exploration of the “peacetime crimes” in Ingeborg Bachmann’s work by offering an analysis of an episode in her novel Malina. Tracing a hitherto unnoticed allusion to a poem by Ungaretti, the analysis also contributes to a discussion of Bachmann’s poetics of citation. The subtle web of intertextual play and citation that pervades the whole novel de-emphasizes the role of the author in literary history and opens instead a reading space where literature as textual memory, again and again, comes to be actualized.